2008
DOI: 10.1111/j.1468-1331.2008.02103.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fatigue on quality of life in patients with Parkinson’s disease

Abstract: Fatigue combined with worse functional status appears to be a significant contributor to poor quality of life. Its multidimensional construct can be used to develop strategies for improving specific aspects of fatigue to improve QoL for PD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
54
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 31 publications
9
54
1
4
Order By: Relevance
“…REM sleep behavioral disorder, restless legs syndrome and periodic movements of the legs are prevalent conditions in PD patients and are putative causes of excessive daytime sleepiness (36). In the present study, fatigue and excessive daytime sleepiness were not associated and the same was observed by others (27,37).…”
Section: Resultssupporting
confidence: 77%
“…REM sleep behavioral disorder, restless legs syndrome and periodic movements of the legs are prevalent conditions in PD patients and are putative causes of excessive daytime sleepiness (36). In the present study, fatigue and excessive daytime sleepiness were not associated and the same was observed by others (27,37).…”
Section: Resultssupporting
confidence: 77%
“…Fatigue was found to be the most frequent of all non-motor symptoms assessed in 1,072 consecutive patients examined in the PRIAMO study [2]. Fatigue also has a significant impact on quality of life [3,4]. In one of the first studies on fatigue in PD, 15-33 % of patients rated it as their most disabling symptom, and more than half rated fatigue among their three worst symptoms [5].…”
Section: Introductionmentioning
confidence: 99%
“…The results of previous studies show that fatigue severity is inversely related to physical activity, functional status, and quality of life (15,17,19,20). It also increases the rate and risk of falls and is highly correlated with fear of falling (18,21).…”
Section: Introductionmentioning
confidence: 88%
“…It is one of the 3 most bothersome symptoms in more than half of PD patients and is the most disabling symptom in 15% -33% of these patients (15). A higher level of fatigue is related to safety concerns, such as a higher risk of falls, cognitive deficits, and reduced quality of life in PD patients (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%